Evaluasi Kinerja Sektor Pertanian dalam Kontribusinya terhadap Pendapatan Nasional dengan Pendekatan Metode Produksi - Nur Syahara Febriana; Hendra Riofita (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
The agricultural sector plays a crucial role in the Indonesian economy, contributing an average of 12.4-13.4% to national GDP in the last decade. This contribution does not only come from on-farm activities but also involves upstream-downstream value chains that can increase economic impacts by more than 20% if they include the processing industry. The research method used to assess the performance of the agricultural sector is descriptive and inferential analysis combined with a quantitative approach. Relevant secondary data sources are the Central Statistics Agency (BPS) and other official sources, including labor data, GDP data, and agricultural commodity production data. Based on the data analyzed, the contribution of the agricultural sector to Indonesia's Gross Domestic Product (GDP) has fluctuated. In 2022, the contribution of the agricultural sector was recorded at 12.40%, although there was a decrease compared to previous years. However, this sector is still able to absorb a significant workforce, with around 28% of the total national workforce involved in it. Evaluation of the performance of the agricultural sector shows that this sector is still an important pillar in the Indonesian economy, with a significant contribution to GDP, labor absorption, and foreign exchange through exports. Despite its fluctuating contribution to GDP and structural challenges such as reliance on conventional production methods, the agricultural sector is competitive in the international market. The plantation and fisheries subsectors are the main contributors to this sector, demonstrating Indonesia's great potential in leading export commodities and maritime resources.